In vitro blood flow in circular PDMS microchannels: effect of the flow rate and hematocrit - Garcia, Valdemar (2010)
Several studies have shown that information obtained on the rheological properties of blood from glass capillaries differs from the situation in vivo [1]. It is therefore important to investigate in vitro blood fluids which have a behavior as close as possible of the in vivo environment.